United States of America. Significant achievements 2014 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamerica de Cooperación para la Agricultura (IICA), 2016)
The main activities carried out by the Institute in the United States during 2014 are identified, with respect to the needs and interests of the country, strengthening on topics such as finance, trade, leadership, public policy, rural development, technology, family farming, food security, by means of the Codex Alimentarius, innovation, gardens and market information systems. Technical cooperation was also provided to small and medium enterprises, water resources management, information management and loss control. Finally, avocado and mango production and in the biological control of tuberculosis were supported.